2011
DOI: 10.4304/tpls.1.3.195-204
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Online Reading Strategies of Adult ESL Learners Using a Learning Management System

Abstract: Abstract-In managing online learning, most educational institutions utilize Learning Management Systems (LMS).It is a learning platform that allows the administrators of the institution to manage and monitor learners, teachers and content of courses. Learners of this online learning environment have access to a variety of online learning tools and features that allow them to communicate with peers as well as instructors. Hence, these learners need to be equipped with appropriate learning strategies, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Other researchers investigating these strategies among EFL students in the Middle East A. Rianto, Indonesian EFL university students' metacognitive online reading strategies before and during the also found that problem-solving strategies were the most frequently used (Darwish, 2017;Mukhlif & Amir, 2017;Omar, 2014). A slightly different result was reported by Ramli et al (2011) who investigated adult students in Malaysia that global reading strategies were more frequently used, followed by problem-solving strategies and support strategies. Furthermore, some of those researchers focused their analyses on differences in the strategy use based on different students' characteristics such as gender, English proficiency level, and level of study.…”
Section: Literature Reviewmentioning
confidence: 60%
See 1 more Smart Citation
“…Other researchers investigating these strategies among EFL students in the Middle East A. Rianto, Indonesian EFL university students' metacognitive online reading strategies before and during the also found that problem-solving strategies were the most frequently used (Darwish, 2017;Mukhlif & Amir, 2017;Omar, 2014). A slightly different result was reported by Ramli et al (2011) who investigated adult students in Malaysia that global reading strategies were more frequently used, followed by problem-solving strategies and support strategies. Furthermore, some of those researchers focused their analyses on differences in the strategy use based on different students' characteristics such as gender, English proficiency level, and level of study.…”
Section: Literature Reviewmentioning
confidence: 60%
“…Taki & Soleimani (2012) reported that male and female students did not differ significantly in using the overall strategy, but they differed significantly in using several individual strategies. Regarding the level of study, Ramli et al (2011) found that the first and second-semester students in Malaysia did not differ significantly in using these three strategy categories. Concerning English proficiency level, Cheng (2016) found that students with intermediate and advanced levels of English proficiency did not differ significantly in using the online reading strategies.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Therefore, online reading issues resulted in need of research of "new digital-and media-literacy strategies" (Kozdras, Welsh, 2008). The research findings on reading in new medium collected by Leu et al (2004), Leu et al(2008), Coiro and Dobler (2007), Kymes (2007), Biancarosa, Griffiths (2012), Hodgson (2010), Ramli et al (2011) indicate that many of the strategies used in print texts can be adapted for the reading of online texts and there is interrelation of online and offline reading behaviours, e.g., students who read a diversity of print material more frequently are also involved in frequent online searching-information activities and more enjoy reading online. However, a more-in depth comparison of print and online reading environments explored by Leu (2002), Hodgson (2010), Kymes (2007), Zhang and Duke (2008), Anderson (2002) suggests that reading skills and strategies can not be simply transferred from the print medium to the online environment as "the online reading requires greater levels of strategic knowledge, and perhaps even different forms of knowledge in order to successfully navigate the increasing amounts of information available in an online global environment" (Kymes, 2007, p. 13).…”
Section: Online Reading Strategies and Metacognitive Awarenessmentioning
confidence: 98%
“…Kymes (2007, p. 16) suggests that "much of the work with online texts has either argued for the possibilities and potentials afforded by these new mediums, compared the new medium (computers) to the old (print texts), or attempted to justify a new and radical approach to teaching literacy". Ramli et al (2011) point at appropriate reading strategies that can lead to success in text comprehension. Therefore, online reading issues resulted in need of research of "new digital-and media-literacy strategies" (Kozdras, Welsh, 2008).…”
Section: Online Reading Strategies and Metacognitive Awarenessmentioning
confidence: 99%
See 1 more Smart Citation